A green neutral state donor-acceptor copolymer for organic solar cells - Gunes, Serap; Baran, Derya; Gunbas, Gorkem; Durmus, Asuman; Fuchsbauer, Anita; Sariciftci, Niyazi Serdar; Toppare, Levent (ROYAL SOC CHEMISTRY, 2010)
We report on the photophysical and photovoltaic properties of a low band gap polymer bearing a quinoxaline moiety, poly(2,3-bis(3,4-bis(decyloxy)phenyl)-5,8-bis(2,3-dihydrothieno[3,4-b][1,4]dioxin-5-yl)quinoxaline) PDOPEQ, as an electron donor in bulk heterojunction solar cells blended with the acceptor 1-(3-methoxycarbonyl)propyl-1-phenyl-[6,6]-methanofullerene (PCBM). Devices were composed of PDOPEQ and varying amounts of PCBM (1 : 1, 1 : 2, 1 : 3, 1 : 4 w-w ratio). The components were spun cast from chlorobenzene (CB) and characterized by measuring current-voltage characteristics under simulated AM 1.5 conditions. The devices with 1: 3 polymer to PCBM ratio exhibited short circuit current density (Jsc) of 0.8 mA cm(-2), an open circuit voltage (Voc) of 0.2 V, and a fill factor (FF) of 0.3. Incident photon to current efficiency (IPCE) is also reported. The IPCE spectrum spans from 400 nm to 800 nm and exhibits a photocurrent contribution of ca. 5.5% at around 400 nm. The nanoscale morphology was investigated with atomic force microscopy (AFM). Photoinduced absorption spectroscopy confirms the photoinduced charge transfer in such donor acceptor blends.
Keywords: BAND-GAP POLYMER; PHOTOVOLTAIC DEVICES; EFFICIENT; THIOPHENE; BENZOTHIADIAZOLE; POLYFLUORENE; TRANSPORT; ELECTRON; PCBM; Polymer Science